Functional expression of the hyperpolarization-activated, non-selective cation current I(f) in immortalized HL-1 cardiomyocytes - Sartiani, Laura (Blackwell Science Inc, 2002)
HL-1 cells are adult mouse atrial myocytes induced to proliferate indefinitely by SV40 large T antigen. These cells beat spontaneously when confluent and express several adult cardiac cell markers including the outward delayed rectifier K(+) channel. Here, we examined the presence of a hyperpolarization-activated I(f) current in HL-1 cells using the whole-cell patch-clamp technique on isolated cells enzymatically dissociated from the culture at confluence. Cell membrane capacitance (C(m)) ranged from 5 to 53 pF. I(f) was detected in about 30 % of the cells and its occurrence was independent of the stage of the culture. I(f) maximal slope conductance was 89.7 ± 0.4 pS pF(−1) (n = 10). I(f) current in HL-1 cells showed typical characteristics of native cardiac I(f) current: activation threshold between −50 and −60 mV, half-maximal activation potential of −83.1 ± 0.7 mV (n = 50), reversal potential at −20.8 ± 1.5 mV (n = 10), time-dependent activation by hyperpolarization and blockade by 4 mm Cs(+). In half of the cells tested, activation of adenylyl cyclase by the forskolin analogue L858051 (20 μm) induced both a ≈6 mV positive shift of the half-activation potential and a ≈37 % increase in the fully activated I(f) current. RT-PCR analysis of the hyperpolarization-activated, cyclic nucleotide-gated channels (HCN) expressed in HL-1 cells demonstrated major contributions of HCN1 and HCN2 channel isoforms to I(f) current. Cytosolic Ca(2+) oscillations in spontaneously beating HL-1 cells were measured in Fluo-3 AM-loaded cells using a fast-scanning confocal microscope. The oscillation frequency ranged from 1.3 to 5 Hz and the spontaneous activity was stopped in the presence of 4 mm Cs(+). Action potentials from HL-1 cells had a triangular shape, with an overshoot at +15 mV and a maximal diastolic potential of −69 mV, i.e. more negative than the threshold potential for I(f) activation. In conclusion, HL-1 cells display a hyperpolarization-activated I(f) current which might contribute to the spontaneous contractile activity of these cells.